Sound Radiation from a Surface Source Located at the Bottom of the Wedge Region - SZEMELA, Krzysztof (Archives of Acoustics, 2015)
Applying rigorous analytical methods, formulas describing the sound radiation have been obtained for the wedge region bounded by two transverse baffles with a common edge and bottom. It has been assumed that the surface sound source is located at the bottom. The presented formulas can be used to calculate the sound pressure and power inside the wedge region. They are valid for any value of the wedge angle and represent a generalization of the formulas describing the sound radiation inside the two and three-wall corner region. Moreover, the presented formulas can be easily adapted for any case when more than one sound source is located at the bottom. To demonstrate their practical application, the distribution of the sound pressure modulus and the sound power have been analyzed in the case of a rectangular piston located at the wedge’s bottom. The influence of the transverse baffle on the sound power has been investigated. Based on the obtained formulas, the behaviour of acoustic fields inside a wedge can be predicted.